MELACAK AKAR KEKERASAN ANTAR AGAMA SEBAGAI DASAR KONFLIK SOSIAL - muchalis muchalis (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2016)
This article will explain about the violence and conflict as the basis of religious learning. It is based on the two main motives: Islam as a universal religion that offers peace and Islam as a solution for the welfare of the poor and a comprehensive religion containing a lot of universal values. Therefore, Islam is not merely religion that discuss issues of economic and political interests, but further it is probably a fundamental foundation in the search for solutions on the basis of violence and social conflicts occur in community. Hence, this paper further describes how Islam as a religion of self-defense may become a way to God (vertical) as the basis for the social problems occur either individually, in groups or both.